The Influence of Price Discount, Free Shipping, and Shopping Lifestyle on Impulsive Buying (Case Study on Shopee Marketplace) - Rahmawati, Heni; Ika Indriasari; Rr. Hawik Ervina Indiworo (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the influence of price discount, free shipping, and shopping lifestyle on impulsive buying. This research method uses quantitative methods. Based on the t test, it can be concluded that the price discount variable has no significant effect on impulsive buying as indicated by a significant value of 0.268 > 0.05. Based on the t test, it can be concluded that the free shipping variable has no significant effect on impulsive buying as indicated by a significant value of 0.963 > 0.05. Based on the t test, it can be concluded that the shopping lifestyle variable has a significant effect on impulsive buying as indicated by a significant value of 0.000 < 0.05. Based on the simultaneous f test, a significant value of 0.000 < 0.05 was obtained, so it can be concluded that price discount, free shipping, and shopping lifestyle as a whole have a significant effect on impulsive buying on the Shopee marketplace.